Separation of Pb2+ and Cu2+ by Zeolite Analcime-Bentonite Composite Membrane - MUTTAQIEN (NIM 10504078), BURHANUDDIN
One of the problem caused by the increase of human population is worse level of water pollution. One of dangerous components of pollutant is heavy metals. Several methods have been used for handling such a pollutant, including the separation method by membrane. In this research, analcime zeolite composite membrane was fabricated for Pb2+ and Cu2+ separation. In this research, the separation carried out could be considered as microfiltration based on the membrane's pore size. Analysis toward permeate and feed phase confirmed a higher rejection coefficient of the membrane towards Pb2+ (92,66%) and a moderate one towards Cu2+ (67,10%). However, their concentration in the feed phase decreased as well. This might be interpreted that there was a phenomenon of absorption of Pb2+ and Cu2+ into the membrane's pores. Thus, an experiment of membrane immersion in a mixture of aqueous Pb2+ and Cu2+ was carried out to determine Pb2+ and Cu2+ content in membrane's pores. It was found that 0.22% Pb2+ and 11.04% Cu2+ were absorbed into the membrane matrix.